Geographic patterns and ecological causes of phylogenetic structure in mosses along an elevational gradient in the central Himalaya - Hong Qian; Oriol Grau (Plant Diversity)
Understanding the underlying mechanisms driving species assembly along elevational gradients is of great interest in ecology and biogeography. The Himalaya is one of the world’s hotspots of biodiversity, and the elevational gradient of the central Himalaya in Nepal is one of the longest elevational gradients in the world. Mosses are important constituents of vegetation in the Himalaya, and knowledge of geographic patterns and ecological causes of phylogenetic structure of mosses along elevational gradients in the Himalaya is critical to understanding the assembly of plant diversity in general, and moss diversity in particular, in the Himalaya. Here, we investigate the relationships of phylogenetic structure metrics reflecting different evolutionary depths with elevation and climatic variables representing mean temperature and precipitation conditions, climate extremes, and climate seasonality for mosses distributed along an elevational gradient spanning about 5000 m in the central Himalaya, Nepal. For a given climatic variable, different metrics of phylogenetic structure show different spatial and climatic patterns, but all phylogenetic metrics standardized for species richness show that phylogenetic dispersion in moss assemblages tend to increase with increasing elevation and decreasing temperature. The standardized effect size of mean pairwise distance of moss assemblages shows a triphasic (zig-zag) pattern, which is generally consistent with the triphasic patterns previously found in angiosperms and ferns along the same elevational gradient. Our study shows that temperature-related variables and climate seasonality variables are more important drivers of phylogenetic dispersion in mosses in Nepal, compared with precipitation-related variables and climate extreme variables, respectively.